PEMBERDAYAAN SOSIAL EKONOMI MASYARAKAT PESISIR DI KELURAHAN KASAWARI KECAMATAN AERTEMBAGA KOTA BITUNG - KONDOY, IVONE; RORONG, ARIE JUNUS; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to find out how the Socio-Economic Empowerment of Coastal Communities in Kasawari Village, Aertembaga District, Bitung City. With the problem of poverty caused by two factors, namely low education and the lack of ability of coastal communities to manage existing natural resources. This study used qualitative methods and the data obtained were analyzed through data reduction, data presentation and conclusion drawing. The informants who were interviewed in this study amounted to six (6) people. There are four (4) indicators that are used as the focus of research, namely: 1) human resources, 2) natural resources, (3) capital, (4) production and marketing infrastructure. Based on the results of the research, the existing empowerment has been going quite well with the assistance and training to develop the capabilities carried out by the local government to reduce poverty with empowerment carried out for coastal communities in Kasawari Village, Aertembaga District, Bitung City. Keywords: Empowerment, Coastal Communities, Poverty